Efficacy in treatment of moderate to severe degree organophosphorus poisoning with fresh frozen plasma, atropine and 2-pyridine aldoxime methyl chloride as compared to treatment with atropine and 2-pyridine aldoxime methyl chloride in Western Odisha - Karua, Purna C.; Parida, Surya K. (International Journal of Research in Medical Sciences, 2020)
Background: Organophosphorus (OP) compounds are one of the most common agents used for suicidal poisoning. People in the middle socioeconomic status are mainly affected. The most important determinant of death in OP poisoning is the severity. The ideal treatment of OP poisoning, this study was undertaken to compare the efficacy of fresh frozen plasma (FFP) along with the standard regimen of atropine and oximes. Methods: 80 patients were taken in this study (40 cases and 40 controls) with history and biochemical pictures suggestive of acute OP poisoning. Normality assumption and equality of variance were satisfied for most of quantitative variables. As a comparison of the baseline data of the study groups did not reveal any significant difference (p>0.05), the result at a given point of time between two groups were also compared with the same methods of assess the comparative changes. Results: Total 80 patients >15 years of age were taken for the study. Out of the total 63.7% are female and 36.3% are males. OP compounds are commonly used as suicidal agent. Salivation is the most common presenting symptoms in both cases and controls. The mean value of serum cholinesterase on day -1 in cases and controls are nearly same but the subsequent mean values as the days progresses are higher in cases than that controls. Conclusions: FFP showed its positive effect in reducing the development of intermediate syndrome/ fatality/ ventilatory support.